Coupling scale-specific habitat selection and activity reveals sex-specific food/cover trade-offs in a large herbivore. (April 2015) - Marchand, Pascal; Garel, Mathieu; Bourgoin, Gilles; Dubray, Dominique; Maillard, Daniel; Loison, Anne
Abstract : The balance between food and perceived predation risk has been revealed as one of the primary drivers of animal habitat selection. However, few studies have investigated how spatiotemporal scales and movement/activity patterns shape responses to this food/cover trade-off while accounting for individual characteristics (e.g. sex) and for variation in predation risk (e.g. hunting) and in resource abundance/quality. We hence studied temporal changes in habitat selection of 30 GPS-collared females and 15 males of Mediterranean mouflon, Ovis gmelini musimon × Ovis sp., at two scales, i.e. 48 h home range selection within a subpopulation area (broad scale) and choice of movement steps (defined as the linear segment between two consecutive locations) according to activity state (fine scale), in southern France. During the hunting-free/food-abundant period, males selected at both scales the foraging habitats providing the best conditions for optimizing their future reproductive success and only selected areas perceived as safe during inactive steps. During the corresponding lambing period, and at both scales, females selected areas perceived as safe that should optimize lamb survival. They switched to the best foraging habitats only when lambs were weaned and only for active steps. By contrast, during hunting, when food was also scarce, both sexes selected home ranges with high proportions of the habitats perceived as safe, in which they performed all their activities. This result suggested that risk avoidance exceeded all the other individual and environmental factors in the hierarchy of the determinants of habitat selection during the hunting period. Coupling scale-specific habitat selection and activity patterns was hence decisive in disclosing how individuals fulfil their specific needs under seasonally changing levels of habitat attributes important for fitness. Highlights: We studied sex-specific habitat selection in mouflon at two spatiotemporal scales. We examined responses to variation in perceived predation risk, food and weather. Both sexes selected cover during the hunting/food-restricted period at both scales. Sex-, scale and activity-specific adjustments rather occurred during spring-summer. Variations in constraints affecting fitness involve changes in habitat selection.